2021
DOI: 10.35882/ijeeemi.v3i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Design a Monitoring Device for Heart-Attack Early Detection Based on Respiration Rate and Body Temperature Parameters

Abstract: Acute myocardial infarction, commonly referred to as a heart attack, is the most common cause of sudden death where a monitoring tool is needed that is equipped with a system that can notify doctors to take immediate action. The purpose of this study was to design a heart attack detection device through indicators of vital human signs. The contribution of this research is that the system works in real-time, has more parameters, uses wireless, and is equipped with a system to detect indications of a heart attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A quick alert of a heart attack can save a patient's life. In [35], a system that monitors heart attacks using indicators of important human signs has been proposed. To detect signs of a heart attack, this system used parameters such as respiration rate and body temperature.…”
Section: Inclusion Criteria (Ic) Ic1mentioning
confidence: 99%
“…A quick alert of a heart attack can save a patient's life. In [35], a system that monitors heart attacks using indicators of important human signs has been proposed. To detect signs of a heart attack, this system used parameters such as respiration rate and body temperature.…”
Section: Inclusion Criteria (Ic) Ic1mentioning
confidence: 99%
“…The electronic circuit of the tool can be seen in FIGURE 3. This tool consists of pulse sensors [13][14][15][16], DS18B20 sensors [17][18][19][20] and Load Cells [21][22][23]. Pulse sensors work by using light.…”
Section: Hardware Designmentioning
confidence: 99%
“…Furthermore, measurement results are also influenced by the device users, for example, the paramedics in hospitals. The paramedics will read the results of the examination measurements to the patient, in this case, the accuracy or inaccuracy of the readings of the measurement results will be determined by the ability of the medical personnel in reading the results [20]. Previous study has found that about 70 percent of the time, these digital devices were not accurate within five mmHg compared to the mercury sphygmomanometer reading (used by medical practitioners) leading to flaws in making informed health decisions.…”
Section: Introductionmentioning
confidence: 99%